Degraded EEG decoding of wrist movements in absence of kinaesthetic feedback. Issue 2 (12th October 2014) - Galán, Ferran; Baker, Mark R.; Alter, Kai; Baker, Stuart N.
Abstract A major assumption of brain–machine interface research is that patients with disconnected neural pathways can still volitionally recall precise motor commands that could be decoded for naturalistic prosthetic control. However, the disconnected condition of these patients also blocks kinaesthetic feedback from the periphery, which has been shown to regulate centrally generated output responsible for accurate motor control. Here, we tested how well motor commands are generated in the absence of kinaesthetic feedback by decoding hand movements from human scalp electroencephalography in three conditions: unimpaired movement, imagined movement, and movement attempted during temporary disconnection of peripheral afferent and efferent nerves by ischemic nerve block. Our results suggest that the recall of cortical motor commands is impoverished in the absence of kinaesthetic feedback, challenging the possibility of precise naturalistic cortical prosthetic control. Hum Brain Mapp 36:643–654, 2015. © 2014 The Authors. Human Brain Mapping Published by Wiley Periodicals, Inc.